161k views
5 votes

f(x)=2(1)/(2) - 3(1)/(3)

User Johnjo
by
6.0k points

1 Answer

2 votes


\huge\textsf{Hey there!}


\mathsf{f(x) = 2(1)/(2)-3(1)/(3)}


\rightarrow\mathsf{y = 2(1)/(2)- 3(1)/(3)}


\rightarrow\mathsf{y = (5)/(2)- (10)/(3)}


\rightarrow\mathsf{y =( (5)/(2)*(3)/(3)) - ((10)/(3)*(2)/(2))}


\mathsf{5*3=\boxed{\bf 15}}\\\\\mathsf{2*3=\boxed{\bf 6}}}\\\\\mathsf{10*2=\boxed{\bf 20}}\\\\\mathsf{3*2=\boxed{\bf 6}}


\rightarrow{\mathsf{y =(15)/(6)-(20)/(6)}


\rightarrow\mathsf{y = (15-20)/(6)}


\mathsf{15-20=\boxed{\bf -5}}\\\\\\\mathsf{6= \boxed{\bf 6}}\textsf{ because \underline{6} is the LCD (\underline{L}east \underline{C}ommon \underline{D}enominator}


\boxed{\mathsf{y =\bf -(5)/(6)}}


\boxed{\boxed{\large\textsf{Answer: \bf y = }\mathsf{\bf -(5)/(6)}}}\huge\checkmark


\large\textsf{Good luck on your assignment and enjoy your day!}

~
\frak{Amphitrite1040:)}

User Fanfavorite
by
6.1k points